Analysis of Use of Virtual Reality Technologies in History Education: A Case Study - YILDIRIM, Gürkan; ELBAN, Mehmet; YILDIRIM, Serkan (Asian Journal of Education and Training, 2018)
Today, many innovations have been experienced in technology. These innovations progressively take their places in education environments. Virtual reality environments are among activity areas that have been frequently discussed and used in education environments in the recent years. In this context, this study aimed to determine general opinions of undergraduate students who were included to study scope about virtual reality technologies, and privately, to determine the students’ opinions about use of virtual reality glasses in history education and to determine their suggestions in this subject. Case study method was preferred in this study. Sampling was created as selecting 25 undergraduate students according to the study purpose. Data was collected with interview technic and analyzed with content analysis method. According to study results, it was concluded that virtual reality implementations were liked by participants. Additionally, participants stated that use of the current technology in course activities would be beneficial. It was thought that especially the feelings of reality and being present in the location, which were caused by virtual reality implementations, were among the factors that affected participants and increased their interest in the course. Moreover, virtual reality implementations were thought to be technologies that could enable the individuals, especially those with disabilities or had different inadequacies (i.e. financial, time etc.), to actively involve in learning processes. Similarly, virtual reality technology was thought to contribute, at least partially, equal opportunities concept in education.